Journeys and travellers in Indian literature and art - Stasik, Danuta; Trynkowska, Anna (Dom Wydawniczy Elipsa, 2018)
The present publication is one of the outcomes of research cooperation spanning two decades in the field of Indian literature and art between the South Asian Studies centres of five academic institutions: University of Milan, Charles University in Prague, Jagiellonian University in Cracow, University of Warsaw and University of Cagliari. The International Seminar 'Journeys and Travellers, Routes and Destinations in Indian Literature and Art', took place on the University of Warsaw premises from 21-23 September 2017. Due to the bulk and broad thematic range of the submitted texts the publication has been divided into two volumes. The first volume contains 13 papers based mostly on Sanskrit and Pali sources, while the second volume includes 12 papers based mostly on sources in vernacular Indian languages. In each volume, the papers have been arranged in roughly chronological order, according to the dating of their sources (although, here and there, the languages of the sources and the specific subjects of the papers have also been taken into consideration). The readers are thus invited to enjoy a journey through time, appropriately for the general topic of the publication.